Handling Slum Settlement Based on Community Participation and Socio–Cultural Change: Perspective of Sustainable Development of Makassar City, Indonesia - Surya, Batara; Salim, Agus; Hernita, Hernita; Suriani, Seri; Abubakar, Herminawaty; Saleh, Haeruddin (Geographica Pannonica, 2021)
Urbanization in the dynamics of development in Makassar City has an impact on increasing population, poverty, social change, acculturation of community culture, marginalization, differences in lifestyle, socio-economic inequality, complexity of space use, slum settlements, and a decrease in environmental quality. This study aims to analyze: (1) Community participation and socio-cultural changes work as determinants of handling urban slum settlements, (2) The influence of community participation, improving the quality of infrastructure, improving the quality of the environment, and changing the socio–cultural community on the sustainability of city development, and (3) Formulate a model for handling slum settlements, community participation, and community social culture towards the sustainability of urban development. This study uses a qualitative-quantitative approach sequentially. Data were obtained through observation, Focus Group Discussions (FGD), surveys, and documentation. The results showed that community participation, improving the quality of infrastructure, improving the quality of the environment, and socio–cultural changes simultaneously affected the sustainability of Makassar City development. Furthermore, the implementation of the program to improve the quality of slums followed by community participation and accompanied by socio-cultural changes will encourage the creation of equitable development, improve the quality of slum settlements, and improve community welfare towards the creation of social cohesion, increase community productivity, and harmonization of community life towards sustainability development of Makassar City, Indonesia.
Keywords: community participation; slums settlements; socio–cultural change; sustainable development.